Current status and relevance of single nucleotide polymorphisms in IL-6-/IL-12-type cytokine receptors. (December 2021) - Scheller, Jürgen; Berg, Anna; Moll, Jens M.; Floss, Doreen M.; Jungesblut, Christopher
Highlights: Algorithm to directly align dbSNP information to DNA and protein sequence. SNP landscape was generated for all tall cytokine receptors of the IL-6/IL-12 family. Structural insights of disease-causing SNPs in cytokine/cytokine receptor interfaces. The algorithm can be easily applied to other cytokine receptor networks. Abstract: Cytokines control immune related events and are critically involved in a plethora of patho-physiological processes including autoimmunity and cancer development. In rare cases, single nucleotide polymorphisms (SNPs) or single nucleotide variations (SNVs) in cytokine receptors eventually cause detrimental ligand-independent, constitutive activation of signal transduction. Most SNPs have, however, no or only marginal influences on gene expression, protein stability, localization and function and thereby only slightly affecting pathogenesis probability. The SNP database (dbSNP) is an archive for a broad collection of polymorphisms in which SNPs are categorized and marked with a locus accession number "reference SNP" (rs). Here, we engineered an algorithm to directly align dbSNP information to DNA and protein sequence information to clearly illustrate a genetic SNP landscape exemplified for all tall cytokine receptors of the IL-6/IL-12 family, including IL-23R, IL-12Rβ1, IL-12Rβ2, gp130, LIFR, OSMR and WSX-1. This information was complemented by a comprehensive literature summary and structural insights of relevant disease-causing SNPs in cytokine/cytokine receptor interfaces. In summary, we present a general strategy with potential to apply to other cytokine receptor networks.